Impact of environmental trend in relation to genotypic and phenotypic trend on traits of economic interest in Kankrej cattle - GUPTA, J P; PRAJAPATI, B M; CHAUDHARI, J D; PANDEY, D P; PANCHASARA, H H; PRAJAPATI, K B (The Indian Journal of Animal Sciences, 2019)
Indiscriminate selection of animals in order to enhance milk production has led to less attention to other traits important in dairying, viz. reproduction; owing to negative association. The production and reproduction records of total 403 Kankrej cows maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, over a period of 35 years from 1979 to 2013, were analyzed to study the production and reproduction traits, viz. 305 day milk yield (305 MY), lactation length (LL), dry period (DP), age at first calving (AFC) and service period (SP). The data were used to investigate the effect of environmental factors as well as estimation of genetic parameters of production and reproduction traits. Genetic, phenotypic and environmental trends were estimated to assess the breeding programme undergoing in the Kankrej herd over the years. The average performance of traits under study was obtained as 2128.64 kg, 282.60 days, 146.13 days, 1366.90 days and 158.06 days for 305 MY, LL, DP, AFC and SP, respectively. The heritability estimates obtained for these traits were 0.31, 0.17, 0.16, 0.05 and 0.96 for 305 MY, LL, DP, SP and AFC respectively. The estimated phenotypic and genetic trends were 7.66 and 23.10 Kg for 305 MY, –0.007 and –0.61 days for LL, 0.022, and –0.032 days for DP, –4.53 and –11.89 days for AFC and –0.07 and –1.61 days for SP, respectively. The results revealed that great improvement in Kankrej herd has been achieved in last 35 years. However, there is further scope of genetic improvement. Designed genetic programme has had great impact on improvement of milk production and AFC but very less impact on the reproductive traits.